A profile shaft connection technique and its applications in transmission structure. (1st January 2014) - Liu, Li; Jia, Wenyou; Xu, Dezhang; Li, Renjun
In this paper, a technique of profile shaft connection is extended to optimise transmission structure for cost reduction, enhancing flexibility and agility, and satisfying mechanical reliability. First, critical parameters and decision-making procedures are addressed. Then two applied cases are investigated. One is four-sided polygon profile shaft connection replacing involute spline connection in washing machine drive system. The other is shaft assembly which can slide and adjust its length in the reconfigurable manufacturing line. The results significantly demonstrate the effectiveness of profile shaft connection.